Assessing in vitro efficacy of certain fungicides to control Sclerotinia sclerotiorum in peanut. (20th January 2019) - Kaur, Gurleen; Lujan, Phillip; Sanogo, Soum; Steiner, Robert; Puppala, Naveen
Abstract: The fungal pathogen Sclerotinia sclerotiorum is responsible for Sclerotinia blight in several crops around the world, including peanut. This study was conducted under laboratory conditions to determine the effects of four registered fungicides, Propulse™, Fontelis ®, Omega ® and Endura ® on mycelial growth and pigmentation, as well as sclerotia and oxalic acid production on a growth medium modified with a fungicide and on the pathogenicity of S. sclerotiorum on leaflets detached from Valencia peanut. Propulse, Omega and Fontelis inhibited mycelial growth of S. sclerotiorum, while, mycelial growth on a modified support with Endura was similar to the control treatment. All fungicides, except Endura, inhibited the production of oxalic acid. Pigmentation of the mycelium was observed in both the control and endura treatments. Sclerotia production was observed only in the control treatment. With the exception of Endura, all fungicides were effective in controlling the development of lesions on Valencia peanut leaflets.